Minimax pattern synthesis with element power constrains for transmitting antenna arrays - Dotlic, Igor; Miura, Ryu (WPMC : 2014 International Symposium on Wireless Personal Multimedia Communications : 7-10 September 2014, Sydney, Australia, 2014)
The paper introduces an efficiency factor useful for the pattern synthesis of the transmitting antenna arrays with each array element being fed by its own power amplifier, active power of which is limited. The factor is based on the L ∞ norm of the active powers at the elements' feeds with mutual coupling between elements taken into account. Two Second Order Cone Programming (SOCP) based methods of the array radiation pattern synthesis that maximize this factor are formulated. After that, minimax array radiation pattern synthesis method with this factor constrained is described. As an illustration of its features, the method is applied on the pattern synthesis of a 15-element antenna array model obtained from the method of moments EM simulation.